A Brief Report about Managing the Spread of COVID-19 with Limited Resources in Bandar Abbas City, South of Iran - Jarineshin, Hashem; Fekrat, Fereydoon; Dalfardi, Behnaz; Khosravi, Fatemeh (Biology, Engineering, Medicine and Science Reports)
Since the end of 2019, the world has experienced the biggest catastrophic event of the century because of the manifestation of novel coronavirus disease (COVID-19). COVID-19 caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which could lead to severe pneumonia. All countries need to prepare their resources and infrastructures as well as healthcare systems to overcome this disaster or any next pandemic, which may occur in the future again. At the time of this writing, my country is suffering from second wave of this pandemic. In Iran, the prevalence of COVID-19 with a high rate of mortality is still at an alarming rate which brings severe concern and a massive burden for health care systems. As of September 15, 2020, the number of infected people with COVID-19 in Iran was 407,353 with 23,453 deaths. In this short report, we want to share our response planning with emphasis on the measures being applied in our hospital particularly our anesthesiology department, to decrease the spread of COVID-19 in the operating rooms and intensive care units (ICU) of this significant referral centre (450-bed) of Hormozgan university located in Bandar Abbas, Hormozgan province south of Iran.
Keywords: COVID-19; Coronavirus disease; Pandemic; Management; Strategies